Soluble Aβ42 Acts as Allosteric Activator of the Core Cholinergic Enzyme Choline Acetyltransferase - Kumar, Amit; Lana, Erica; Kumar, Rajnish; Lithner, Christina Unger; Darreh-Shori, Taher (Frontiers in Molecular Neuroscience, 2018)
Two major questions in the field of Alzheimer-type dementia remain elusive. One is the native function of Amyloid-beta (Aβ) peptides and the other is an early deficit in the central cholinergic network. Nevertheless, recent evidence suggests that Aβ peptides are involved in the regulation of acetylcholine (ACh) homeostasis either by allosteric activation of ACh-degrading cholinesterases or by inhibiting the high-affinity choline uptake transporter. In the current study, we report that Aβ peptides, in particular, Aβ42 allosterically enhances the catalytic rate of the core-cholinergic enzyme choline acetyltransferases (ChAT), responsible for biosynthesis of ACh. Detailed in vitro enzyme kinetic analysis indicated that both soluble A40 and A42 enhanced the catalytic efficiency of ChAT by ~ 21 % and 26% at physiological concentration ranges found in human cerebrospinal fluids (CSF). Further analyses indicated that activation of ChAT by Aβ was highly specific. Intriguingly, A42 exhibited an EC50 of activation potency at tenfold lower concentrations compared to A40. The activation was persistent even in the presence of a physiological Aβ 40/42 mixture ratio, expected in human CSF. In conclusion, we report for the first time that A42 peptide acts as allosteric enhancers of ACh-biosynthesizing enzyme ChAT. Together with two previous observations, this points to a complex molecular cross-talk between Aβ and the enzymatic machinery involved in maintaining cellular, synaptic and extra-synaptic ACh homeostasis, warranting further investigation.